An extract of Pueraria tuberosa tubers attenuates diabetic nephropathy by upregulating matrix metalloproteinase‐9 expression in the kidney of diabetic rats: 野荸荠块茎提取物通过上调糖尿病大鼠肾脏中基质金属蛋白酶‐9的表达来延缓糖尿病肾病. (13th April 2016) - Tripathi, Yamini B.; Shukla, Rashmi; Pandey, Nidhi; Pandey, Vivek; Kumar, Mohan
Abstract: Background: Currently, no drug is available to directly target the signaling molecules involved in the pathogenesis of diabetic nephropathy (DN); only antihypertensive and antidiabetic drugs are in clinical use. In the present study, the therapeutic effects of a active fraction of tubers from Pueraria tuberosa (hereafter referred to as PTY‐2) were investigated in streptozotocin (STZ)‐diabetic rats with DN, with particular emphasis on its effects on extracellular matrix (ECM) accumulation and matrix metalloproteinase (Mmp)‐9 expression in kidney tissue. Methods: Rats were injected with 55 mg/kg, i.p., STZ. After 40 days, rats were divided into groups as follows (n = 6 per group): Group 1, age‐matched rats not injected with STZ (non‐diabetic control); Group 2, STZ‐diabetic DN rats; and Group 3, PTY‐2 (30 mg/100 g, p.o.)‐treated DN rats. After 20 days treatment, the effects of PTY‐2 on serum urea and creatinine concentrations, urinary levels of glucose, creatinine, protein, and ketone bodies, and urine pH were determined. Kidney tissue was evaluated for Mmp‐9 expression and histological changes. Results: Blood glucose, serum urea, creatinine, and urine protein levels were significantly higher, and creatinine clearance was significantly lower, in Group 2 versus Group 1 rats. There was a higher degree of glomerulosclerosis, expansion of the mesangial matrix, and excess ECM deposition and eosinophilic casts in kidneys from Group 2 versus Group 1 rats. Furthermore, Mmp‐9 activity and expression were significantly reduced in kidney homogenate of Group 2 versus Group 1 rats. Interestingly, PTY‐2 treatment significantly reversed all these changes in DN rats. Conclusion: Treatment of DN rats with PTY‐2 significantly attenuated the severity of DN by increasing the expression and activity of Mmp‐9, consequently degrading the ECM accumulated in kidney tissue. Highlights: New herbal to prevent progressive diabetic nephropathy. It attenuates glomerulosclerosis by activating Mmp‐9 Thin sections of kidneys from (a) non‐diabetic control rats (Group 1), (b) untreated streptozotocin‐diabetic rats with diabetic nephropathy (DN; Group 2) and (c) DN rats treated with 30 mg/kg PTY‐2, an active fraction extracted from tubers of Pueraria tuberosa (Group 3). (a) In sections from Group 1 rats, renal parenchyma with a normal glomerulus (G) and tubules (T) was seen, with normal epithelium. (b) In Group 2 rats, the glomerulus had widened capillaries (arrow), irregular attachment to Bowman's capsule, and there was cloudy swelling in the tubules with deposition of eosinophilic casts (EC; thick arrow). (c) In Group 3, PTY‐2 treatment significantly improvement the changes seen in untreated DN rats. (Hematoxylin and eosin staining; original magnification ×400.)